Characterization of soft magnetic materials at low frequency - Atika Arshad (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
The use of sensor technology from today's application view point has renewed research interest in studying magnetic material from a perspective different from what such materials were studied for in the recent past. The use of portable and implanted devices is on the rise, mostly for monitoring biomedical parameters. Biomedical signals are of low frequency and low amplitude. The electronic components used for sensing of such signals include inductive magneto-inductive transducers. This requirement necessitates the study of the magnetic materials and its characterization at low frequencies. This is done through simulation while obtaining distinctive hysteresis loops for magnetic materials. The simulation results are validated by obtaining experimental hysteresis loops. The simulation and practical validation of the materials under study are further complemented by using another novel circuit for obtaining distinctive impedance peaks. The consistency in between the aluminum and steel core hysteresis loops is further verified by observing a similar consistency in between the impedance peaks of these materials. It should be mentioned that high impedance peaks mean high output voltage in the secondary side. The novelty of this technique lies in the use of experimental setup made from ordinary and easily electronic components. As a whole, this work aims to investigate and characterize magnetic and non-magnetic materials; thus opening up a new branch of research for the application of soft magnetic materials in biomedical field. The results for magnetic materials have shown a dominant behavior over the results obtained for non-magnetic materials due to larger permeability value and magnetic strength.